The Effectiveness of Timor Local Wisdom-Based Fantasy Digital Comics in Improving Seventh-Grade Junior High School Students’ Reading Literacy - Adriani Laiskodat; C. Asri Budiningsih (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
Improving students’ reading literacy has become an important challenge in Indonesian language learning, particularly in fantasy story materials that require imaginative and interpretative abilities. This study aimed to evaluate the effectiveness of a Timor local wisdom-based fantasy digital comic in improving the reading literacy of seventh-grade students at SMP Negeri Satu Atap Fatukoto. The research employed a One-Group Pretest-Posttest design involving 29 students. Data were collected through pretest and posttest assessments and analyzed using parametric statistics, paired sample t-tests, and N-Gain. The digital comic media was validated by material experts, cultural experts, and media experts, achieving an average feasibility score of 94.0%, categorized as highly feasible. The findings revealed a significant improvement in students’ reading literacy skills, with the average pretest score increasing from 43.8 to a posttest score of 83.1. The paired sample t-test showed t = -17.239; p < 0.001, while the N-Gain score of 0.7 was categorized as high. Improvements were identified across three main PISA 2022 literacy indicators: locating information, understanding text content, and evaluating and reflecting on reading materials. These findings indicate that Timor local wisdom-based digital comics are effective in improving reading literacy while simultaneously introducing and preserving local culture in junior high school Indonesian language learning.